IMPLEMENTASI PERATURAN DAERAH KABUPATEN TANGERANG NOMOR 7 TAHUN 2019 TENTANG PERLINDUNGAN PEREMPUAN DAN ANAK DALAM TINDAK KEKERASAN - Cahyaningtiyas, Tri Lulu; Bangsawan, Try Adhi; Amilia, Rizki (Gapenas Publisher, 2025)
The purpose of this study is to determine the effectiveness of Regional Regulation No. 7 of 2018 concerning the Prevention of Violence against Women and Children. Specifically, the Women's Empowerment and Child Protection Agency (DP3A) of Tangerang Regency is the subject of this study. The ability to report crimes of violence against children and women is an obstacle for many victims of violence. Patriarchal culture, peer pressure, and economic limitations play a role in this. It is based on these concerns that this research was established. This qualitative descriptive study uses recording, participant observation, and interviews to collect its results. Bureaucratic structure, communication, resources, and implementer disposition are four important indicators that form George C. Edward III's policy implementation model, which is the theory applied in this study. This study found that there are still various challenges in the implementation of Regional Regulations, one of which is the lack of infrastructure resources, the lack of public understanding of violence, and the reluctance of victims to report because they still consider reporting violence to be very taboo.